Creating value added to customers: Marketing and sales role - Damnjanović Vesna; Filipović Vinka (Marketing (Beograd. 1991), 2006)
This paper presents the new trends in sales and marketing areas which reshaping markets and changing the way business is done. Marketing and sales management need a well-defined strategy for added value exploration, creation and delivery. The holistic marketing process involves all stakeholders and required them to participate in the value added creation process.